Analysis of the content of I-FABP in urine and blood serum in children with gastrointestinal food allergy - N. G. Prikhodchenko; T. A. Shumatova; A. Nee; E. S. Zernova (Медицинский совет, 2021)
Abstract Introduction. Protein-induced enteropathy is one of the common manifestations of gastrointestinal food allergy in young children. The search of non-invasive methods for intestine estimation is especially relevant for early diagnosis and timely prevention of exacerbation.The aim of the study was to determine the serum and urinal levels of the intestinal fraction of the protein binding fatty acids in children with protein-induced enteropathy and to evaluate their clinical and diagnostic significance.Materials and methods. It was examined 36 children with protein-induced enteropathy aged 1.5 months to 1 year and 20 healthy children (control group). All patients underwent esophagogastroenteroscopy with morphological examination of biopsy specimens for differential diagnosis with congenital gastrointestinal diseases. The Cow’s Milk-related Symptom Score (CoMMiS) was used to evaluate clinical symptoms. The intestinal fraction of a fatty acid binding protein was determined for all children in blood serum, urine by enzyme- linked immunosorbent analysis.Results. It was found the increase its serum level (125.20 ± 23.79 pg / ml), and urinal level (0.164 ± 0.031 pkg / ml) compared with the control group (19.21 ± 4.94 pg / ml, 00.039 ± 4.62 pkg / ml, respectively, p < 0.05). There were found direct strong correlations between the severity of gastrointestinal manifestations and its serum and urine level (p < 0.05).Discussion. Epithelial barrier damage provides an increased penetration of intact food allergens. It plays a key role in allergic sensitization, and it is the first pathogenetic link of allergic inflammation in most cases. A statistically significant I-FABP increased level in all studied biological fluids correlates with morphological changes in the children with protein-induced enteropathy, as well as with clinical symptoms of gastrointestinal tract lesions. That confirms its high informational value for an indirect assessment of the state of the intestinal barrier.Conclusions. Thus, an increase in serum and urinal I-FABP levels in children with protein-induced enteropathy confirms the clinical and diagnostic significance of determining this biomarker in all biological fluids. Its high sensitivity and specificity of determination in urine are promising for use in pediatric practice.